Temperature-Driven Transcriptomic Regulation of Xylogenesis in Gigantochloa levis Reveals Transcriptional Suppression of Secondary Cell Wall Biosynthetic Programs under Heat Stress - Mohammad Rahmat Derise; Anis Adilah Mustafa; Kenneth Francis Rodrigues; Julius Kulip; Chee Wei Yew; Wilson Thau Lym Yong (Plant Molecular Biology Reporter, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Combined Toxicity of PFAS and Microplastics in Aquatic Ecosystems: Synergistic, Additive, and Antagonistic Interactions - Efe Jeffery Isukuru; Obaro Wilson Isaiah; Victor Okpanachi; Mariam Toyin Okunade; Adeyemi Abejoye; Ann Ogechi Felix; Agada Felix Ojochegbe; Blessing Oby Okoye; Chioma C. Nwakanobi; Olumide Abayomi Ige; Kenneth N. Kikanme (Water, Air, & Soil Pollution, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Acoustic Monitoring of Two Seagrass Meadows Reveals Differences in Oxygen Ebullition and Biomass - Megan S. Ballard; Kyle A. Capistrant-Fossa; Kevin M. Lee; Andrew R. McNeese; Colby W. Cushing; Robert T. Taylor; Thomas S. Jerome; Kenneth H. Dunton; Preston S. Wilson (Estuaries and Coasts, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Protein Crystallization in Microgravity: Commercialization and the Next Chapter - Molly K. Mulligan; Stephen Tuma; Sara Mullins; Kenneth A. Savin; Anne Wilson (Current Stem Cell Reports, 2025)
The purpose of this review is to describe the benefit of growing crystals in a microgravity environment and the changes we are seeing in this field. The advantages of crystal growing in microgravity has been discussed, investigated and utilized for academic and industrial purposes since the mid 1950’s. The benefits for growing crystals in a microgravity environment have been supported through the individual studies and the meta-analysis that has been executed for the purposes of recent reviews. Recent findings suggest there is a change in the targets and applications of Protein Crystal Growth (PCG) in microgravity. As the space program looks to refocus its resources on exploration and industry experts start to see the benefit of doing work in microgravity, there has been a shift towards a more commercial emphasis on the way PCG programs are run and the goals of those programs. This shift has led to changes in the landscape for this exciting and potentially profitable area of space-based research. In summary, herein we describe the changes we are seeing and share some of our own results and the results from other groups. We believe that these results support the shifts and inform the new directions we believe this field is going to take in the coming years and the impact it will have on the utilization of space grown crystals.

Introducing ‘miniRECgap’ R package for simple gap-filling of missing eddy covariance CO2 flux measurements with classic nonlinear environmental response functions via GUI-supported R-scripts (case-study: In-sample gap-filling with ‘miniRECgap’ vs. MDS and an optimised shallow ANN in a ‘challenging’ peatland ecosystem) - Alina Premrov; Jagadeesh Yeluripati; Richard Slevin; Adam Bates; Magdalena Matysek; Stephen Barry; Kenneth A. Byrne; Rowan Fealy; Bernard Hyde; Gary Lanigan; Mark McCorry; Rachael Murphy; et al. (Environmental Modelling & Software, 2025)

Biogeochemical controls on iron speciation and cycling across upland to shoreline gradients in freshwater and estuarine coastal soils (Lake Erie and Chesapeake Bay, United States) - Lucie Stetten; Maxim I. Boyanov; Edward J. O'Loughlin; Shan Pushpajom Thomas; Kathleen R. Beilsmith; Roberta B. Peixoto; Fausto Machado-Silva; Donnie J. Day; Stephanie J. Wilson; Timothy W. Vugteveen; Allison N. Myers-Pigg; Opal Otenburg; et al. (Science of The Total Environment, 2025)

Native mid-gut bacterial community increases resistance to nucleopolyhedrovirus in the cotton leafworm - Tong Li; Yueli Jiang; Yunhui Zhang; Yuqing Wu; Kenneth Wilson; Pengjun Xu (Pesticide Biochemistry and Physiology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Membrane filtration for enumeration of Listeria monocytogenes at low levels on salad leaf - Nicola Wilson; Karin Goodburn; Kenneth Johnston (Food Control, 2024)

Active afforestation of drained peatlands is not a viable option under the EU Nature Restoration Law - Gerald Jurasinski; Alexandra Barthelmes; Kenneth A. Byrne; Bogdan H. Chojnicki; Jesper Riis Christiansen; Kris Decleer; Christian Fritz; Anke Beate Günther; Vytas Huth; Hans Joosten; Radosław Juszczak; Sari Juutinen; et al. (Ambio, 2024)
The EU Nature Restoration Law (NRL) is critical for the restoration of degraded ecosystems and active afforestation of degraded peatlands has been suggested as a restoration measure under the NRL. Here, we discuss the current state of scientific evidence on the climate mitigation effects of peatlands under forestry. Afforestation of drained peatlands without restoring their hydrology does not fully restore ecosystem functions. Evidence on long-term climate benefits is lacking and it is unclear whether CO 2 sequestration of forest on drained peatland can offset the carbon loss from the peat over the long-term. While afforestation may offer short-term gains in certain cases, it compromises the sustainability of peatland carbon storage. Thus, active afforestation of drained peatlands is not a viable option for climate mitigation under the EU Nature Restoration Law and might even impede future rewetting/restoration efforts. Instead, restoring hydrological conditions through rewetting is crucial for effective peatland restoration.

Seaweed: A bioindustrial game-changer for the green revolution - Wilson Thau Lym Yong; Vun Yee Thien; Mailin Misson; Grace Joy Wei Lie Chin; Siti Nahdatul Isnaini Said Hussin; Harry Lye Hin Chong; Nur Athirah Yusof; Nyuk Ling Ma; Kenneth Francis Rodrigues (Biomass and Bioenergy, 2024)

Anti-cytomegalovirus antibody levels stratify human immune profiles across the lifespan - Makiko Watanabe; Lisa Davidson; Patricia Smith; Peter F. Castellucio; Mladen Jergovic; Jennifer L. Uhrlaub; Megan J. Smithey; Lori E. Fantry; Brett Dechambre; Rachel C. Wilson; Kenneth C. Knox; Jie Ren; et al. (GeroScience, 2024)

Assessing the impact of soil and field conditions on cotton crop emergence using UAV-based imagery - Fengkai Tian; Curtis J. Ransom; Jianfeng Zhou; Bradley Wilson; Kenneth A. Sudduth (Computers and Electronics in Agriculture, 2024)

Camp Lejeune Marine Cancer Risk Assessment for Exposure to Contaminated Drinking Water From 1955 to 1987 - Paul E. Rosenfeld; Kenneth R. Spaeth; Savannah J. McCarthy; Sophia C. Winter; Maddie S. Wilson; Matthew Hagemann (Water, Air, & Soil Pollution, 2024)
This study utilizes guidance from the United States Environmental Protection Agency (USEPA) and the Agency for Toxic Substances and Disease Registry (ATSDR) to calculate the cancer risk to United States Marines who were exposed to carcinogens in drinking water at Marine Corps Base Camp Lejeune. Camp Lejeune is a 233-square-mile Marine Corps training facility in North Carolina. From 1953 to 1987, nearby dry cleaners, landfills, and underground storage tanks contaminated drinking water systems that served Camp Lejeune (ATSDR, 2017). Some of the most toxic contaminants found in the drinking water modeled by ATSDR include benzene, tetrachloroethylene (PCE), trichloroethylene (TCE), trans-1,2-dichloroethylene (DCE), and vinyl chloride (VC). ATSDR utilized MODFLOW and EPANET modeling software to determine the level of contamination in the three main drinking water systems at Camp Lejeune: Tarawa Terrace, Holcomb Boulevard, and Hadnot Point. This paper presents an application of methodology to quantify cancer risk for the Marines who lived and served at Camp Lejeune from 1953 to 1987 using ATSDR’s health assessment, chemical contaminant modeling, and USEPA methodology. While VC and TCE were found to be the main risk drivers, benzene and PCE also contributed to the cumulative cancer risk. This analysis shows (1) That the cancer risk was greatest during the 1970s and 1980s and (2) that the inhalation exposure pathway had the greatest contribution to overall cancer risk followed by ingestion, with the smallest contribution from dermal absorption.

Climate change perception and adaptation strategies to multiple climatic hazards: Evidence from the northeast of Thailand - Salinda Sedtha; Malay Pramanik; Sylvia Szabo; Kenneth Wilson; Kwang Soon Park (Environmental Development, 2023)

Adapting the CROPGRO Perennial Forage model to predict growth and development of Pensacola bahiagrass - Hunter D. Smith; Chris H. Wilson; Stuart J. Rymph; Erick R.S. Santos; Kenneth J. Boote (Field Crops Research, 2023)

Characteristics of upward-connecting-leader current leading to attachment in downward negative cloud-to-ground lightning strokes - Amitabh Nag; Kenneth L. Cummins; Mathieu N. Plaisir; Robert G. Brown; Jennifer G. Wilson; David E. Crawford; R. Carl Noggle; Hamid K. Rassoul (Atmospheric Research, 2023)

Global genomic signature reveals the evolution of fall armyworm in the Eastern hemisphere - Lei Zhang; Zaiyuan Li; Yan Peng; Xinyue Liang; Kenneth Wilson; Gilson Chipabika; Patrick Karangwa; Bellancile Uzayisenga; Benjamin A. Mensah; Donald L. Kachigamba; Yutao Xiao (Molecular Ecology, 2023)
The major plant pest fall armyworm (FAW), Spodoptera frugiperda, is native to the Americas and has colonized Africa and Asia within the Eastern hemisphere since 2016, causing severe damage to multiple agricultural crop species. However, the genetic origin of these invasive populations requires more in‐depth exploration. We analysed genetic variation across the genomes of 280 FAW individuals from both the Eastern hemisphere and the Americas. The global range‐wide genetic structure of FAW shows that the FAW in America has experienced deep differentiation, largely consistent with the Z‐chromosomal Tpi haplotypes commonly used to differentiate ‘corn‐strain’ and ‘rice‐strain’ populations. The invasive populations from Africa and Asia are different from the American ones and have a relatively homogeneous population structure, consistent with the common origin and recent spreading from Africa to Asia. Our analyses suggest that north‐ and central American ‘corn‐strain’ FAW are the most likely sources of the invasion into the Eastern hemisphere. Furthermore, evidence based on genomic, transcriptomic and mitochondrial haplotype network analyses indicates an earlier, independent introduction of FAW into Africa, with subsequent migration into the recent invasive population.

Physiological phenotypes have optimal values relevant to healthy aging: sweet spots deduced from the Canadian Longitudinal Study on Aging - Olga Vishnyakova; Xiaowei Song; Kenneth Rockwood; Lloyd T. Elliott; Angela Brooks-Wilson (GeroScience, 2023)
Previous observations on a group of exceptionally healthy “Super-Seniors” showed a lower variance of multiple physiological measures relevant for health than did a less healthy group of the same age. The finding was interpreted as the healthier individuals having physiological measurement values closer to an optimal level, or “sweet spot.” Here, we tested the generalizability of the sweet-spot hypothesis in a larger community sample, comparing differences in the variance between healthier and less healthy groups. We apply this method to the Canadian Longitudinal Study on Aging (CLSA) comprehensive cohort of 30,097 participants aged 45 to 85 years with deep phenotype data. Data from both sexes and four age ranges were analyzed. Five instruments were used to represent different aspects of health, physical, and cognitive functioning. We tested 231 phenotypic measures for lower variance in the most healthy vs. least healthy quartile of each sex and age group, as classified by the five instruments. Segmented regression was used to determine sex-specific optimal values. One hundred forty-two physiological measures (61%) showed lower variance in the healthiest than in the least healthy group, in at least one sex and age group. The difference in variance was most significant for hemoglobin A1c and was also significant for many body composition measurements, but not for bone mineral density. Ninety-four phenotypes showed a nonmonotonic relationship with health, consistent with the idea of a sweet spot; for these, we determined optimal values and 95% confidence intervals that were generally narrower than the ranges of current clinical reference intervals. These findings for sweet spot discovery validate the proposed approach for identifying traits important for healthy aging.

The impact of field margins on biological pest control: a meta-analysis - Lucy I. Crowther; Kenneth Wilson; Andrew Wilby (BioControl, 2023)
Floral field margins are known to benefit invertebrate species diversity and abundance within agricultural landscapes, but variation in success limits widespread uptake. Understanding how variation within floral field margins can affect certain entomological groupings is lacking but would allow for a more individualised design of margins to enhance biological control. This meta-analysis aims to answer the question; do floral field margins benefit biological pest control over grassy field margins? We found that floral margins significantly benefit the natural enemy community and biological control services, relative to non-floral grass margins. We confirm that field margin type is linked to higher abundance and diversity of natural enemies, lower numbers of herbivorous invertebrate pests, and reduced crop damage. We consider whether specific characterisations of natural enemies and pest communities vary between these margin types, finding key differences in the abundances of aerial and epigeal enemies, the diversity of parasitoid and predatory enemies and pest abundances found in naturally regenerating and sown floral field margins. The finding here cements the implementation of floral field margins as a legitimate control method for crop pests in the face of losses due to pesticides and highlights design and management considerations for the success of floral margins.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Soil organic carbon stocks by soil group for afforested soils in Ireland - Caren Jarmain; Thomas Cummins; Antonio Jonay Jovani-Sancho; Tim Nairn; Alina Premrov; Brian Reidy; Florence Renou-Wilson; Brian Tobin; Kilian Walz; David Wilson; Kenneth A. Byrne (Geoderma Regional, 2023)

T-cell cellular stress and reticulocyte signatures, but not loss of naïve T lymphocytes, characterize severe COVID-19 in older adults - Mladen Jergović; Makiko Watanabe; Ruchika Bhat; Christopher P. Coplen; Sandip A. Sonar; Rachel Wong; Yvonne Castaneda; Lisa Davidson; Mrinalini Kala; Rachel C. Wilson; Homer L. Twigg; Kenneth Knox; et al. (GeroScience, 2023)

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Recent advances in seaweed seedling production: a review of eucheumatoids and other valuable seaweeds - Calvin Jiksing; McMarshall M. Ongkudon; Vun Yee Thien; Kenneth Francis Rodrigues; Wilson Thau Lym Yong (Algae, 2022)
Modern seaweed farming relies heavily on seedlings from natural beds or vegetative cuttings from previous harvests. However, this farming method has some disadvantages, such as physiological variation in the seed stock and decreased genetic variability, which reduces the growth rate, carrageenan yield, and gel strength of the seaweeds. A new method of seedling production that is sustainable, scalable, and produces a large number of high-quality plantlets is needed to support the seaweed farming industry. Recent use of tissue culture and micropropagation techniques in eucheumatoid seaweed production has yielded promising results in increasing seed supply and growing uniform seedlings in large numbers in a shorter time. Several seaweed species have been successfully cultured and regenerated into new plantlets in laboratories using direct regeneration, callus culture, and protoplast culture. The use of biostimulants and plant growth regulators in culture media increases the seedling quality even further. Seedlings produced by micropropagation grew faster and had better biochemical properties than conventionally cultivated seedlings. Before being transferred to a land-based grow-out system or ocean nets for farming, tissue-cultured seedlings were recommended to undergo an acclimatization process to increase their survival rate. Regular monitoring is needed to prevent disease and pest infestations and grazing by herbivorous fish and turtles during the farming process. The current review discusses recent techniques for producing eucheumatoid and other valuable seaweed farming materials, emphasizing the efficiency of micropropagation and the transition from laboratory culture to cultivation in land-based or open-sea grow-out systems to elucidate optimal conditions for sustainable seaweed production.

Spatial Distribution of Heavy Metals in Near-Shore Marine Sediments of the Jeddah, Saudi Arabia Region: Enrichment and Associated Risk Indices - Riyadh F. Halawani; Myra E. Wilson; Kenneth M. Hamilton; Fahed A. Aloufi; Md. Abu Taleb; Aaid G. Al-Zubieri; Andrew N. Quicksall (Journal of Marine Science and Engineering, 2022)
Red Sea coastal development has rapidly accelerated in recent decades that has led to a rise in the anthropogenic heavy metal levels in sediments. A total of 80 surficial sediment samples were collected from the shallow waters along the eastern Red Sea coast near Jeddah, Saudi Arabia. These samples were collected from three locations, designated as North, Middle and South of Jeddah, to assess the concentrations of six heavy metals: chromium (Cr), manganese (Mn), nickel (Ni), copper (Cu), zinc (Zn), and lead (Pb). The results showed that the concentrations (mg/kg) of these metals in the studied sediments follow this order: Pb (77.34 ± 150.59) > Mn (36.52 ± 37.72) > Zn (18.02 ± 23.94) > Cr (9.56 ± 5.81) > Cu (9.18 ± 13.67) > Ni (3.68 ± 4.54). The majority of the polluted sediments were recorded in the Middle and South locations. Pollution and enrichment indices such as Geo-accumulation indices (Igeo), Enrichment Factors (Ef), Contamination Factors (Cf), Pollution Load Indices (PLI), Potential Ecological Risk Indices (PERI) and Potential Toxicity Response Indices (RI) were calculated from the measured metals to establish baselines for the region and assess specific metal enrichments by location along the Jeddah coastline. The Igeo values showed that 30% of the Southern location stations are considered moderately to highly polluted. The Ef for all the studied sediments followed this order: Pb (extremely severe enrichment) > Zn > Cu > Cd > Cr (severe enrichment) > Ni (moderate enrichment).

A trait‐based model ensemble approach to design rice plant types for future climate - Livia Paleari; Tao Li; Yubin Yang; Lloyd T. Wilson; Toshihiro Hasegawa; Kenneth J. Boote; Samuel Buis; Gerrit Hoogenboom; Yujing Gao; Ermes Movedi; Françoise Ruget; Upendra Singh; et al. (Global Change Biology, 2022)
Crop models are powerful tools to support breeding because of their capability to explore genotype × environment×management interactions that can help design promising plant types under climate change. However, relationships between plant traits and model parameters are often model specific and not necessarily direct, depending on how models formulate plant morphological and physiological features. This hinders model application in plant breeding. We developed a novel trait‐based multi‐model ensemble approach to improve the design of rice plant types for future climate projections. We conducted multi‐model simulations targeting enhanced productivity, and aggregated results into model‐ensemble sets of phenotypic traits as defined by breeders rather than by model parameters. This allowed to overcome the limitations due to ambiguities in trait‐parameter mapping from single modelling approaches. Breeders' knowledge and perspective were integrated to provide clear mapping from designed plant types to breeding traits. Nine crop models from the AgMIP‐Rice Project and sensitivity analysis techniques were used to explore trait responses under different climate and management scenarios at four sites. The method demonstrated the potential of yield improvement that ranged from 15.8% to 41.5% compared to the current cultivars under mid‐century climate projections. These results highlight the primary role of phenological traits to improve crop adaptation to climate change, as well as traits involved with canopy development and structure. The variability of plant types derived with different models supported model ensembles to handle related uncertainty. Nevertheless, the models agreed in capturing the effect of the heterogeneity in climate conditions across sites on key traits, highlighting the need for context‐specific breeding programmes to improve crop adaptation to climate change. Although further improvement is needed for crop models to fully support breeding programmes, a trait‐based ensemble approach represents a major step towards the integration of crop modelling and breeding to address climate change challenges and develop adaptation options.

The decreased PG content of pgp1 inhibits PSI photochemistry and limits reaction center and light-harvesting polypeptide accumulation in response to cold acclimation - Alexander G. Ivanov; Marianna Krol; Leonid V. Savitch; Beth Szyszka-Mroz; Jessica Roche; D. P. Sprott; Eva Selstam; Kenneth W. Wilson; Richard Gardiner; Gunnar Öquist; Vaughan M. Hurry; Norman P. A. Hüner (Planta, 2022)

The understudied links of the retromer complex to age-related pathways - Kenneth A. Wilson (GeroScience, 2022)
Neuronal aging is associated with numerous diseases resulting in memory impairment and functional decline. A common hallmark of these disorders is the accumulation of intracellular and extracellular protein aggregates. The retromer complex plays a central role in sorting proteins by marking them for reuse rather than degradation. Retromer dysfunction has been shown to induce protein aggregates and neurodegeneration, suggesting that it may be important for age-related neuronal decline and disease progression. Despite this, little is known about how aging influences retromer stability and the proteins with which it interacts. Detailed insights into age-dependent changes in retromer structure and function could provide valuable information towards treating and preventing many age-related neurodegenerative disorders. Here, we visit age-related pathways which interact with retromer function that ought to be further explored to determine its role in age-related neurodegeneration.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Factors influencing distributional shifts and abundance at the range core of a climate‐sensitive mammal - Peter D. Billman; Erik A. Beever; David B. McWethy; Lindsey L. Thurman; Kenneth C. Wilson (Global Change Biology, 2021)
Species are frequently responding to contemporary climate change by shifting to higher elevations and poleward to track suitable climate space. However, depending on local conditions and species’ sensitivity, the nature of these shifts can be highly variable and difficult to predict. Here, we examine how the American pika ( Ochotona princeps ), a philopatric, montane lagomorph, responds to climatic gradients at three spatial scales. Using mixed‐effects modeling in an information‐theoretic approach, we evaluated a priori model suites regarding predictors of site occupancy, relative abundance, and elevational‐range retraction across 760 talus patches, nested within 64 watersheds across the Northern Rocky Mountains of North America, during 2017–2020. The top environmental predictors differed across these response metrics. Warmer temperatures in summer and winter were associated with lower occupancy, lower relative abundances, and greater elevational retraction across watersheds. Occupancy was also strongly influenced by habitat patch size, but only when combined with climate metrics such as actual evapotranspiration. Using a second analytical approach, acute heat stress and summer precipitation best explained retraction residuals (i.e., the relative extent of retraction given the original elevational range of occupancy). Despite the study domain occurring near the species’ geographic‐range center, where populations might have higher abundances and be at lower risk of climate‐related stress, 33.9% of patches showed evidence of recent extirpations. Pika‐extirpated sites averaged 1.44℃ warmer in summer than did occupied sites. Additionally, the minimum elevation of pika occupancy has retracted upslope in 69% of watersheds (mean: 281 m). Our results emphasize the nuance associated with evaluating species’ range dynamics in response to climate gradients, variability, and temperature exceedances, especially in regions where species occupy gradients of conditions that may constitute multiple range edges. Furthermore, this study highlights the importance of evaluating diverse drivers across response metrics to improve the predictive accuracy of widely used, correlative models.

Toward a better understanding of fish‐based contribution to ocean carbon flux - Grace K. Saba; Adrian B. Burd; John P. Dunne; Santiago Hernández‐León; Angela H. Martin; Kenneth A. Rose; Joseph Salisbury; Deborah K. Steinberg; Clive N. Trueman; Rod W. Wilson; Stephanie E. Wilson (Limnology and Oceanography, 2021)
Fishes are the dominant vertebrates in the ocean, yet we know little of their contribution to carbon export flux at regional to global scales. We synthesize the existing information on fish‐based carbon flux in coastal and pelagic waters, identify gaps and challenges in measuring this flux and approaches to address them, and recommend research priorities. Based on our synthesis of passive (fecal pellet sinking) and active (migratory) flux of fishes, we estimated that fishes contribute an average (± standard deviation) of about 16.1% (± 13%) to total carbon flux out of the euphotic zone. Using the mean value of model‐generated global carbon flux estimates, this equates to an annual flux of 1.5 ± 1.2 Pg C yr −1 . High variability in estimations of the fish‐based contribution to total carbon flux among previous field studies and reported here highlight significant methodological variations and observational gaps in our present knowledge. Community‐adopted methodological standards, improved and more frequent measurements of biomass and passive and active fluxes of fishes, and stronger linkages between observations and models will decrease uncertainty, increase our confidence in the estimation of fish‐based carbon flux, and enable identification of controlling factors to account for spatial and temporal variability. Better constraints on this key component of the biological pump will provide a baseline for understanding how ongoing climate change and harvest will affect the role fishes play in carbon flux.

Summary of Findings and Research Recommendations from the Gulf of Mexico Research Initiative - Charles Wilson; Michael Feldman; Michael Carron; Nilde Dannreuther; Kenneth Halanych; Jennifer Petitt; Jürgen Rullkötter; Paul Sandifer; Kevin Shaw; John Shepherd; David Westerholm; Callan Yanoff; et al. (Oceanography, 2021)
Following the Deepwater Horizon explosion and oil spill in 2010, the Gulf of Mexico Research Initiative (GoMRI) was established to improve society’s ability to understand, respond to, and mitigate the impacts of petroleum pollution and related stressors of the marine and coastal ecosystems. This article provides a high-level overview of the major outcomes of the scientific work undertaken by GoMRI. This initiative contributed to significant knowledge advances across the physical, chemical, geological, and biological oceanographic research fields, as well as in related technology, socioeconomics, human health, and oil spill response measures. For each of these fields, this paper outlines key advances and discoveries made by GoMRI scientists (along with a few surprises), synthesizing their efforts in order to highlight lessons learned, future research needs, remaining gaps, and suggestions for the next generation of scientists.

Impacts of Petroleum, Petroleum Components, and Dispersants on Organisms and Populations - Steven Murawski; Martin Grosell; Cynthia Smith; Tracey Sutton; Kenneth Halanych; Richard Shaw; Charles Wilson (Oceanography, 2021)
Following the Deepwater Horizon blowout, oil, degraded oil, oil mixed with dispersants, and management responses to the spill affected a variety of Gulf of Mexico organisms. This review provides examples of various documented impacts, common patterns, and trends across organisms and/or their environments, and discusses future implications as well as directions for future research. Organism effects are generally characterized as lethal and sublethal. Sublethal can be short term, long term, or permanent and multigenerational. We present individual examples of effects on behavioral response, olfaction, vision, cardiac function, and gene shift, based on research done in laboratories, mesocosm settings, and the field. Future research should emphasize collection and analysis of routine toxicological baselines and examine how and if molecular impacts cascade up to populations. This research will require development of rapid molecular tools and testing procedures to determine exposure compared to field-relevant exposure levels and to be able to extrapolate laboratory results to the field, especially given the mosaic of differing contaminant concentrations (below, at, or exceeding critical concentrations that result in lethal or sublethal effects) occurring in the environment. Recent chemical studies have identified a detectable suite of polycyclic aromatic hydrocarbon metabolites for which there are no toxicity data; further research is needed to determine their impacts on food webs.

Cryo-imaging of Stem Cell Biodistribution in Mouse Model of Graft-Versus-Host-Disease - Patiwet Wuttisarnwattana; Saada Eid; Madhusudhana Gargesha; Kenneth R. Cooke; David L. Wilson (Annals of Biomedical Engineering, 2020)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Survival costs of reproduction are mediated by parasite infection in wild Soay sheep - Jessica A. Leivesley; Luc F. Bussière; Josephine M. Pemberton; Jill G. Pilkington; Kenneth Wilson; Adam D. Hayward (Ecology Letters, 2019)
A trade‐off between current and future fitness potentially explains variation in life‐history strategies. A proposed mechanism behind this is parasite‐mediated reproductive costs: individuals that allocate more resources to reproduction have fewer to allocate to defence against parasites, reducing future fitness. We examined how reproduction influenced faecal egg counts ( FEC ) of strongyle nematodes using data collected between 1989 and 2008 from a wild population of Soay sheep in the St. Kilda archipelago, Scotland (741 individuals). Increased reproduction was associated with increased FEC during the lambing season: females that gave birth, and particularly those that weaned a lamb, had higher FEC than females that failed to reproduce. Structural equation modelling revealed future reproductive costs: a positive effect of reproduction on spring FEC and a negative effect on summer body weight were negatively associated with overwinter survival. Overall, we provide evidence that parasite resistance and body weight are important mediators of survival costs of reproduction.

Hypersalinity During Regional Drought Drives Mass Mortality of the Seagrass Syringodium filiforme in a Subtropical Lagoon - Sara S. Wilson; Kenneth H. Dunton (Estuaries and Coasts, 2018)

Nutritional composition of honey bee food stores vary with floral composition - Philip Donkersley; Glenn Rhodes; Roger W. Pickup; Kevin C. Jones; Eileen F. Power; Geraldine A. Wright; Kenneth Wilson (Oecologia, 2017)

Introduction to the Special Issue: An Overview of the Gulf of Mexico Research Initiative - John Shepherd; Debra Benoit; Kenneth Halanych; Michael Carron; Rick Shaw; Chuck Wilson (Oceanography, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Long‐range seasonal migration in insects: mechanisms, evolutionary drivers and ecological consequences - Jason W. Chapman; Don R. Reynolds; Kenneth Wilson (Ecology Letters, 2015)
Myriad tiny insect species take to the air to engage in windborne migration, but entomology also has its ‘charismatic megafauna’ of butterflies, large moths, dragonflies and locusts. The spectacular migrations of large day‐flying insects have long fascinated humankind, and since the advent of radar entomology much has been revealed about high‐altitude night‐time insect migrations. Over the last decade, there have been significant advances in insect migration research, which we review here. In particular, we highlight: (1) notable improvements in our understanding of lepidopteran navigation strategies, including the hitherto unsuspected capabilities of high‐altitude migrants to select favourable winds and orientate adaptively, (2) progress in unravelling the neuronal mechanisms underlying sun compass orientation and in identifying the genetic complex underpinning key traits associated with migration behaviour and performance in the monarch butterfly, and (3) improvements in our knowledge of the multifaceted interactions between disease agents and insect migrants, in terms of direct effects on migration success and pathogen spread, and indirect effects on the evolution of migratory systems. We conclude by highlighting the progress that can be made through inter‐phyla comparisons, and identify future research areas that will enhance our understanding of insect migration strategies within an eco‐evolutionary perspective.

Establishment and Short-term Productivity of Annual and Perennial Bioenergy Crops Across a Landscape Gradient - Danielle M. Wilson; Emily A. Heaton; Lisa A. Schulte; Theodore P. Gunther; Monika E. Shea; Richard B. Hall; William Landon Headlee; Kenneth J. Moore; Nicholas N. Boersma (BioEnergy Research, 2014)

Occupational exposure and ovarian cancer risk - Nhu D. Le; Andy Leung; Angela Brooks-Wilson; Richard P. Gallagher; Kenneth D. Swenerton; Paul A. Demers; Linda S. Cook (Cancer Causes & Control, 2014)

Optimization of culture conditions for the direct regeneration of Kappaphycus alvarezii (Rhodophyta, Solieriaceae) - Wilson Thau Lym Yong; Siew Hoo Ting; Yoong Soon Yong; Vun Yee Thien; Siew Hie Wong; Wei Lie Chin; Kenneth Francis Rodrigues; Ann Anton (Journal of Applied Phycology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Performance of species richness estimators across assemblage types and survey parameters - Gordon C. Reese; Kenneth R. Wilson; Curtis H. Flather (Global Ecology and Biogeography, 2014)
Aim A raw count of the species encountered across surveys usually underestimates species richness. Statistical estimators are often less biased. Nonparametric estimators of species richness are widely considered the least biased, but no particular estimator has consistently performed best. This is partly a function of estimators responding differently to assemblage‐level factors and survey design parameters. Our objective was to evaluate the performance of raw counts and nonparametric estimators of species richness across various assemblages and with different survey designs. Location We used both simulated and published field data. Methods We evaluated the bias, precision and accuracy of raw counts and 13 nonparametric estimators using simulations that systematically varied assemblage characteristics (number of species, species abundance distribution, total number of individuals, spatial configuration of individuals and species detection probability), sampling effort and survey design. Results informed the development of an estimator selection framework that we evaluated with field data. Results When averaged across assemblages, most nonparametric estimators were less negatively biased than a raw count. Estimators based on the similarity of repeated subsets of surveys were most accurate and their accumulation curves appeared to reach asymptotes fastest. Number of species, species abundance distribution and effort had the largest effects on performance, ultimately by affecting the proportion of the species pool contained in a sample. Our estimator selection framework showed promising results when applied to field data. Main conclusions A raw count of the number of species in an area is far from the best estimate of true species richness. Nonparametric estimators are less biased. Newer largely unused, estimators perform better than more well known and longer established counterparts under certain conditions. Given that there is generally a trade‐off between bias and precision, we believe that estimator variance, which is often not reported when presenting species richness estimates, should always be included.

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

Effect of pH on neutral lipid and biomass accumulation in microalgal strains native to the Canadian prairies and the Athabasca oil sands - Blair Skrupski; Kenneth E. Wilson; Kira L. Goff; Jitao Zou (Journal of Applied Phycology, 2013)

The PSBP2 protein of Chlamydomonas reinhardtii is required for singlet oxygen-dependent signaling - Pawel Brzezowski; Kenneth E. Wilson; Gordon R. Gray (Planta, 2012)

An acoustic investigation of seagrass photosynthesis - Christopher J. Wilson; Preston S. Wilson; Kenneth H. Dunton (Marine Biology, 2012)

W olbachia in a major African crop pest increases susceptibility to viral disease rather than protects - Robert I. Graham; David Grzywacz; Wilfred L. Mushobozi; Kenneth Wilson (Ecology Letters, 2012)
W olbachia are common vertically transmitted endosymbiotic bacteria found in S podoptera exempta ), which show that the prevalence and intensity of infection with a nucleopolydrovirus ( SpexNPV ) is positively associated with infection with three strains of W olbachia . We also use laboratory bioassays to demonstrate that infection with one of these strains, a male‐killer, increases host mortality due to SpexNPV by 6–14 times. These findings suggest that rather than protecting their lepidopteran host from viral infection, W olbachia instead make them more susceptible. This finding potentially has implications for the biological control of other insect crop pests.

Mixotrophic and photoautotrophic cultivation of 14 microalgae isolates from Saskatchewan, Canada: potential applications for wastewater remediation for biofuel production - Kyoung C. Park; Crystal Whitney; Jesse C. McNichol; Kathryn E. Dickinson; Scott MacQuarrie; Blair P. Skrupski; Jitao Zou; Kenneth E. Wilson; Stephen J. B. O’Leary; Patrick J. McGinn (Journal of Applied Phycology, 2012)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

Explosive Pleistocene range expansion leads to widespread Amazonian sympatry between robust and gracile capuchin monkeys - Jessica W. Lynch Alfaro; Jean P. Boubli; Link E. Olson; Anthony Di Fiore; Bryan Wilson; Gustavo A. Gutiérrez‐Espeleta; Kenneth L. Chiou; Meredith Schulte; Sarah Neitzel; Vanessa Ross; Doreen Schwochow; Mai T.T. Nguyen; et al. (Journal of Biogeography, 2012)
Aim Capuchin monkey species are widely distributed across Central and South America. Morphological studies consistently divide the clade into robust and gracile forms, which show extensive sympatry in the Amazon Basin. We use genetic data to test whether Miocene or Plio‐Pleistocene processes may explain capuchin species’ present distributions, and consider three possible scenarios to explain widespread sympatry. Location The Neotropics, including the Amazon and Atlantic Coastal Forest. Methods We sequenced the 12S ribosomal RNA and cytochrome b genes from capuchin monkey specimens. The majority were sampled from US museum collections and were wild‐caught individuals of known provenance across their distribution. We applied a Bayesian discrete‐states diffusion model, which reconstructed the most probable history of invasion across nine subregions. We used comparative methods to test for phylogeographic association and dispersal rate variation. Results Capuchins contained two well supported monophyletic clades, the morphologically distinct ‘gracile’ and ‘robust’ groups. The time‐tree analysis estimated a late Miocene divergence between Cebus and Sapajus and a subsequent Plio‐Pleistocene diversification within each of the two clades. Bayesian analysis of phylogeographic diffusion history indicated that the current wide‐ranging sympatry of Cebus and Sapajus across much of the Amazon Basin was the result of a single explosive late Pleistocene invasion of Sapajus from the Atlantic Forest into the Amazon, where Sapajus is now sympatric with gracile capuchins across much of their range. Main conclusions The biogeographic history of capuchins suggests late Miocene geographic isolation of the gracile and robust forms. Each form diversified independently, but during the Pleistocene, the robust Sapajus expanded its range from the Atlantic Forest to the Amazon, where it has now encroached substantially upon what was previously the exclusive range of gracile Cebus . The genus Cebus , as currently recognized, should be split into two genera to reflect the Miocene divergence and two subsequent independent Pliocene radiations: Cebus from the Amazon and Sapajus from the Atlantic Forest.

Development and characterization of twelve polymorphic microsatellite loci in the Bog Copper, Lycaena epixanthe - Sarah P. Flanagan; W. Herbert Wilson; Kenneth L. Jones; Stacey L. Lance (Conservation Genetics Resources, 2010)

Temporal production of the two Bacillus anthracis siderophores, petrobactin and bacillibactin - Melissa K. Wilson; Rebecca J. Abergel; Jean E. L. Arceneaux; Kenneth N. Raymond; B. Rowe Byers (BioMetals, 2010)

Pathogen persistence in migratory insects: high levels of vertically-transmitted virus infection in field populations of the African armyworm - Luisa Vilaplana; Kenneth Wilson; Elizabeth M. Redman; Jenny S. Cory (Evolutionary Ecology, 2010)

Lack of reinforcement enhancing effects of nicotine in non-dependent smokers - Kenneth A. Perkins; Amy Grottenthaler; Annette S. Wilson (Psychopharmacology, 2009)

Climate change and the spread of infectious ideas - Kenneth Wilson (Ecology, 2009)

Ocean barriers and glaciation: evidence for explosive radiation of mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis (Mollusca, Nudibranchia) - NERIDA G. WILSON; M. SCHRÖDL; KENNETH M. HALANYCH (Molecular Ecology, 2009)
Strong currents and deep passages of water can be barriers for larval dispersal of continental marine animals, but potential effects on direct developers are under‐investigated. We examined the genetic structure of Doris kerguelenensis , a directly developing sea slug that occurs across the Drake Passage, the body of water separating Antarctica from South America. We found deep mitochondrial divergences within populations on both sides of the Drake Passage, and South American animals formed multiple sister‐group relationships with Antarctic animals. A generalised molecular clock suggested these trans‐Drake pairs diverged during the Pliocene–Pleistocene, after the formation of the Drake Passage. Statistical parsimony methods recovered 29 separate haplotype networks (many sympatric) that likely correlate with allopatric events caused by repeated glacial cycles. Data from 16S were congruent but more conserved than COI, and the estimated ancestral 16S haplotype was widespread. The marked difference in the substitution rates between these two mitochondrial genes results in different estimates of connectivity. Demographic analyses on networks revealed some evidence for selection and expanding populations. Contrasting with the Northern Hemisphere, glaciation in Antarctica appears to have increased rather than reduced genetic diversity. This suggests orbitally forced range dynamics based on Northern Hemisphere phylogeography do not hold for Antarctica. The diverse lineages found in D. kerguelenensis point towards a recent, explosive radiation, likely reflecting multiple refuges during glaciation events, combined with limited subsequent dispersal. Whether recognised as cryptic species or not, genetic diversity in Antarctic marine invertebrates appears higher than expected from morphological analyses, and supports the Antarctic biodiversity pump phenomenon.

Initial nicotine sensitivity in humans as a function of impulsivity - Kenneth A. Perkins; Caryn Lerman; Sarah B. Coddington; Christopher Jetton; Joshua L. Karelitz; John A. Scott; Annette S. Wilson (Psychopharmacology, 2008)

Density-related variation in vertical transmission of a virus in the African armyworm - Lluisa Vilaplana; Elizabeth M. Redman; Kenneth Wilson; Jenny S. Cory (Oecologia, 2008)

Methane flux dynamics in an Irish lowland blanket bog - Anna Laine; David Wilson; Gerard Kiely; Kenneth A. Byrne (Plant and Soil, 2007)

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Reliability and Validity of an Assessment of Usual Phytoestrogen Consumption (United States) - Pamela L. Horn-Ross; Stephen Barnes; Valerie S. Lee; Christine N. Collins; Peggy Reynolds; Marion M. Lee; Susan L. Stewart; Alison J. Canchola; Landon Wilson; Kenneth Jones (Cancer Causes & Control, 2006)

Hereditary prostate cancer in Finland: fine-mapping validates 3p26 as a major predisposition locus - Annika Rökman; Agnes B. Baffoe-Bonnie; Elizabeth Gillanders; Henna Fredriksson; Ville Autio; Tarja Ikonen; Kenneth D. Gibbs; MaryPat Jones; Derek Gildea; Diane Freas-Lutz; Carol Markey; Mika P. Matikainen; et al. (Human Genetics, 2005)

Starvation Induced Alterations in Hepatic Lysine Metabolism in Different Families of Rainbow Trout (Oncorhynchus mykiss) - Angela D. Higgins; Jeffrey T. Silverstein; Juanita Engles; Matthew E. Wilson; Caird E. Rexroad; Kenneth P. Blemings (Fish Physiology and Biochemistry, 2005)

Temperature-induced greening of Chlorella vulgaris . The role of the cellular energy balance and zeaxanthin-dependent nonphotochemical quenching - Kenneth E. Wilson; Marianna Krl; Norman P. A. Huner (Planta, 2003)

Melanism and disease resistance in insects - Kenneth Wilson; Sheena C. Cotter; Andrew F. Reeson; Judith K. Pell (Ecology Letters, 2001)
There is growing evidence that insects in high‐density populations invest relatively more in pathogen resistance than those in low‐density populations (i.e. density‐dependent prophylaxis). Such increases in resistance are often accompanied by cuticular melanism, which is characteristic of the high‐density form of many phase polyphenic insects. Both melanism and pathogen resistance involve the prophenoloxidase enzyme system. In this paper the link between resistance, melanism and phenoloxidase activity is examined in Spodoptera larvae. In S. exempta , cuticular melanism was positively correlated with phenoloxidase activity in the cuticle, haemolymph and midgut. Melanic S. exempta larvae were found to melanize a greater proportion of eggs of the ectoparasitoid Euplectrus laphygmae than non‐melanic larvae, and melanic S. littoralis were more resistant to the entomopathogenic fungus Beauveria bassiana (in S. exempta the association between melanism and fungal resistance was non‐signficant). These results strengthen the link between melanism and disease resistance and implicate the involvement of phenoloxidase.

Quitting cigarette smoking produces minimal loss of chronic tolerance to nicotine - Kenneth Perkins; Debra Gerlach; Michelle Broge; Mark Sanders; James Grobe; Carolyn Fonte; Christine Cherry; Annette Wilson; Rolf Jacob (Psychopharmacology, 2001)

Threshold doses for nicotine discrimination in smokers and non-smokers - Kenneth A. Perkins; Carolyn Fonte; Mark Sanders; Jennifer Meeker; Annette Wilson (Psychopharmacology, 2001)

The role of growth rate, redox-state of the plastoquinone pool and the trans-thylakoid ΔpH in photoacclimation of Chlorella vulgaris to growth irradiance and temperature - Kenneth E. Wilson; Norman P. A. Huner (Planta, 2000)

Characterization of 14 tetranucleotide microsatellite loci derived from sockeye salmon - Jeffrey B. Olsen; Sheri L. Wilson; Eric J. Kretschmer; Kenneth C. Jones; James E. Seeb (Molecular Ecology, 2000)

Characterization of 14 tetranucleotide microsatellite loci derived from sockeye salmon - Jeffrey B. Olsen; Sheri L. Wilson; Eric J. Kretschmer; Kenneth C. Jones; James E. Seeb (Molecular Ecology, 2000)

Effects of central and peripheral nicotinic blockade on human nicotine discrimination - Kenneth A. Perkins; Mark Sanders; Carolyn Fonte; Annette S. Wilson; Wendy White; Richard Stiller; Dennis McNamara (Psychopharmacology, 1999)

Localised Cerebral Phosphorus-31 MR Spectroscopy in Man Before and Immediately after Coronary Bypass Surgery with Hypothermic Cardiopulmonary Bypass - Jason A. Wilson; Simon D. Taylor-Robinson; David J. Bryant; Kenneth M. Taylor; David N. F. Harris (Metabolic Brain Disease, 1998)

Genetic variation in the genus Bufo I. An extreme degree of transferrin and albumin polymorphism in a population of the American toad (Bufo americanus) - Sheldon I. Guttman; Kenneth G. Wilson (Biochemical Genetics, 1973)